Integrating Green IT into IS/IT Strategic Planning: A Ward and Peppard Framework for Sustainable Digital Transformation in Higher Education - Pujiono, Agung; Samopa, Febriliyan; Rabiula, Andre; Fikri Muhammad , Khalis Fikri; Haryus Wirasapta, Andicho (Jurusan Pendidikan Teknik Elektro, 2026)
The development of information systems and information technology (IS/IT) has significantly transformed higher education; however, inadequate strategic planning often leads to inefficiencies and environmental impacts, such as high energy consumption and electronic waste. Despite the growing importance of sustainability, existing IS/IT strategic planning approaches generally do not explicitly integrate environmental considerations, thus creating a gap between digital transformation and sustainability objectives. This study aims to develop an IS/IT strategic planning framework that integrates green IT principles within the Ward and Peppard methodology. A qualitative case study approach was applied at Akademi Farmasi Yarsi Pontianak using data collected through interviews, observations, and questionnaires. The analysis incorporated multiple frameworks, including the Balanced Scorecard, PEST, Porter’s Five Forces, SWOT, and Critical Success Factors. The results produced integrated IS/IT strategies that align organizational goals with sustainability principles, including the development of information systems, environmentally oriented IT infrastructure, and governance mechanisms that support green IT implementation. The findings indicate that integrating green IT into IS/IT strategic planning can enhance operational effectiveness while contributing to environmental sustainability. This study contributes by extending the Ward and Peppard framework through the explicit incorporation of environmental sustainability as a strategic dimension, providing a practical and replicable model for higher education institutions pursuing sustainable digital transformation.